Síntese, caracterizaҫão e reatividade de novos complexos de rutênio do tipo cis-[Ru(bpy)2L(X)](PF6)n (n= 1 e 3), bpy=2,2’-BIPIRIDINA, X=Cl− , NO2− , NO+ e L= 4-phpy e 4-pybz - Manigat, Woodruff (2023)
Coordination compounds based on Ru(II) metal center have presented biological activities and applications for various diseases such as cancer, cardiovascular diseases (DCV), parasitosis, etc. Additionally, metallocomplex NO donors have been widely studied successfully as nitric oxide releasing agents, allowing them to act as pro-drugs stimulated by chemical or photochemical reduction to supplement nitric oxide deficiency that is associated with certain pathological states. Nitrosyl metal coordination compounds are successfully used as metallodrugs in the treatment of DCV, cancer etc. In view of the facts mentioned, this work aims to synthesize, characterize and study the reactivity of new ruthenium complexes of the type cis-[Ru(bpy)2L(X)](PF6)n (n=1 ou 3), bpy=2,2’- bipyridine, X= Cl−, NO2−, NO+ and L= 4- phenylpyridine (4-phpy) and analogue 4-pyridyl benzimidazole (4-pybz). The characterization was performed through vibrational spectroscopic techniques in the infrared region, uv-visible as well as computer simulations, 1H nuclear magnetic resonance and cyclic voltametry, supporting the proposed structures. The nitrosyl summed up complexes were then analyzed as to their ability to release nitric oxide (NO°) under different conditions. Spectroscopic follow-up during electrical potential application and under light irradiation (λirr=460nm) indicated the formation of aque-complex, suggesting the release of NOo. cPTIO was also used as a probe for detection of nitric oxide and indicated the release of NO/HNO after irradiation. Furthermore, nitrosyl complexes are likely to release NO/HNO when they react with thiol reducers (L-cysteine). Through the nitrosyl/nitro interconveration study for complexes cis-[Ru(NO)(bpy)2(4-phpy)]3+e cis-[Ru(NO)(bpy)2(4-pybz)]3+, it was found that the complexes react with the OH-ion forming the respective complex nitrite and that this reaction is reversible by pH adjustment. The first complex has an inflection point with pH and balance 2.10 and the second has two points of inflections with equilibrium pH 1,16 e 6,02. In the vascular relaxation test, the complexes cis-[Ru(NO2)(bpy)2(4-phpy)]+e cis-[Ru(NO2)(bpy)2(4-pybz)]+ are very promising, demonstrating excellent hypotensive activity.